THE INFLUENCE OF FOOD QUALITY, PRICE, LOCATION, AND ENVIRONMENT ON CONSUMER SATISFACTION AT DAJA HOUSE RESTAURANT, LAMPUNG - Arditanojo, Edward Bryan; Arnis, Nindya Yuliani; Wuisan, Dewi (Indonesian Marketing Journal, 2023)
This study aims to analyze the influence of food quality, price, location, and environment on consumer satisfaction at Daja House Restaurant in Lampung City. The study was conducted with customers who had visited the restaurant at least three times within a six-month period. The research used a quantitative method with purposive sampling, targeting Daja House Restaurant customers. Data was collected through questionnaires distributed via Google Forms. A total of 55 valid responses were received. The data was then processed using SmartPLS 4.0 software for testing indicator validity, variable reliability, and the research model using R². The results showed that food quality had no significant effect on consumer satisfaction. However, location and environment were found to have a positive influence on consumer satisfaction, and price also had a positive effect on consumer satisfaction. Based on these findings, the study recommends that the restaurant's management pay more attention to the location and environment in terms of the restaurant's facilities and atmosphere to attract more consumers. In addition, the price should remain affordable to maintain consumer satisfaction. Therefore, the management should continue to ensure that the prices offered to consumers are reasonable.